Empowering Learners on Mathematic Subject by Problem Based Learning and Metacognitive Strategy to Improve Reflective Thinking Competence - Ghofur, Abd; Andawiyah, Rofiatul; Mattari , Ali Said Al (Yayasan Corolla Education Centre, 2023)
Learning on math in the classroom has a one way teacher center, so the student will be un-active, the process of learning on math that could be done more concentrate on finishing the test that has procedural character only, that caused the student couldn’t finished a math problem that usually applied in the class, didn’t give a chance for the student to develop their competence of thinking, in which, one of them is reflective thinking competence. The fact above be an early thinking for the researcher, while the objective of the research will be focused on knowing the implementation of problem base learning and metacognitive in improving mathematic reflective thinking competence, analysing the lacknes on the implementation of problem based learning and metacognitive in improving mathematic reflective thinking competence, knowing the advantages based learning and metacognitive in improving mathematic reflective thinking. Research approach that used in this research is descriptive qualitative approach, by the setting of the research is SMK1 Pamekasan, with the math teacher and the student as the subject of the research. In data analysis, the researcher used Miles model. The result shown that teaching learning activities became more active, the students have developed thinking skills, enabling them to find the appropriate ways to solve the problems they face. The thinking process involved enables the students to solve mathematical problems and has a connection with their ability to remember and recognize relationships between mathematical concepts, understand cause-and-effect relationships, analogies or differences.